2002
DOI: 10.1136/bjo.86.9.951
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of blindness and low vision in Malaysian population: results from the National Eye Survey 1996

Abstract: Br J Ophthalmol 2002;86:951-956 Background: A national eye survey was conducted in 1996 to determine the prevalence of blindness and low vision and their major causes among the Malaysian population of all ages. Methods: A stratified two stage cluster sampling design was used to randomly select primary and secondary sampling units. Interviews, visual acuity tests, and eye examinations on all individuals in the sampled households were performed. Estimates were weighted by factors adjusting for selection proba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
90
4
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(105 citation statements)
references
References 6 publications
8
90
4
3
Order By: Relevance
“…15 We expected a strong correlation between age and visual impairment but as mentioned earlier, this relationship was only observed in women. In men, visual impairment did not have a significant relationship with age.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…15 We expected a strong correlation between age and visual impairment but as mentioned earlier, this relationship was only observed in women. In men, visual impairment did not have a significant relationship with age.…”
Section: Discussionmentioning
confidence: 80%
“…In most reports, especially from East Asian countries, cataract has been introduced as the first cause of visual impairment. 14,27,33,34 In some reports like Harbin from China, 34 it has been shown that cataract is responsible for 70% of the cases of bilateral blindness.…”
Section: Discussionmentioning
confidence: 99%
“…Cataract is a leading cause of blindness in Malaysia (39%) [1] . A dropped nucleus is a nightmare for any cataract surgeon.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] The World Health Organization (WHO) estimated that in 2004, there were 153 million people in the world who were visually impaired by uncorrected refractive errors. 19 For this reason, refractive errors are among the conditions targeted by Vision 2020: The Right to Sight, a global initiative organized by the WHO and the International Agency for the Prevention of Blindness with the aim of eliminating avoidable forms of blindness.…”
Section: Introductionmentioning
confidence: 99%